Variability in drought incidence over India -A statistical approach (MAUSAM, 1989)
Based on the monsoon rainfall for 113 years (18.75-1987), an attempt has been made to quantify drought for the country as a whole and identify drought years by developing a drought index. For this purpose total area of India receiving monsoon rainfall less than 75% of the normal was obtained for each of the 113 years. From this, meal1 drought affected area and Its standard deviation were worked out. The difference between area affected by drought In any year and the 113 years' mean drought area divided by the standard deviation was detained as drought index. Time interval between successive drought years has been subjected to statistical analysis and the distribution determined and tested for randomness. The series of drought years, was also subjected to return period analysis. Within the analysed time frame, 1918 is found to be the worst drought in India. It is observed that India can sometimes even experience spells of three successive years of drought of varying intensity and extent. The time interval between successive drought years can be approximately described by Poisson's distribution.